Mapping of the human plasmin domain recognized by the unique plasmin receptor of group A streptococci. - Broder, C C (1989)
A high-affinity surface receptor for human plasmin has been reported on certain group A streptococci. To map the region of the plasmin molecule that binds to the bacterial receptor, isolated domains of plasmin were tested for their ability to inhibit the binding of intact radiolabeled plasmin to receptor-positive bacteria. Complete inhibition of binding of labeled plasmin to bacteria by isolated heavy chains was achieved, but this inhibition was not as efficient on a molar basis when compared with that of unlabeled plasmin. By contrast, a conformationally altered form of native plasminogen was found to bind to bacteria and was as efficient a competitive inhibitor as intact plasmin was. The results of this study indicate that the selective binding of human plasmin to a group A streptococcus is dependent on structures present in the conformationally altered form of native plasminogen or plasmin that are not found on the native zymogen, the plasminogen with NH2-terminal glutamic acid.